Teamwork among midwives during neonatal resuscitation at a maternity hospital in Nepal. Issue 3 (June 2017) - Wrammert, Johan; Sapkota, Sabitri; Baral, Kedar; KC, Ashish; Målqvist, Mats; Larsson, Margareta
Abstract: Problem: The ability of health care providers to work together is essential for favourable outcomes in neonatal resuscitation, but perceptions of such teamwork have rarely been studied in low-income settings. Background: Neonatal resuscitation is a proven intervention for reducing neonatal mortality globally, but the long-term effects of clinical training for this skill need further attention. Having an understanding of barriers to teamwork among nurse midwives can contribute to the sustainability of improved clinical practice. Aim: To explore nurse midwives' perceptions of teamwork when caring for newborns in need of resuscitation. Methods: Nurse midwives from a tertiary-level government hospital in Nepal participated in five focus groups of between 4 and 11 participants each. Qualitative Content Analysis was used for analysis. Findings: One overarching theme emerged: looking for comprehensive guidelines and shared responsibilities in neonatal resuscitation to avoid personal blame and learn from mistakes . Participants discussed the need for protocols relating to neonatal resuscitation and the importance of shared medical responsibility, and the importance of the presence of a strong and transparent leadership. Discussion: The call for clear and comprehensive protocols relating to neonatal resuscitation corresponded with previous research from different contexts. Conclusion: Nurse midwives working at a maternity health care facility in Nepal discussed the benefits and challenges of teamwork in neonatal resuscitation. The findings suggest potential benefits can be made from clarifying guidelines and responsibilities in neonatal resuscitation. Furthermore, a structured process to deal with clinical incidents must be considered. Management must be involved in all processes.